Retinoic acid receptor-related orphan receptor α regulates bystander activation of memory CD8+ T cells - Cai, Zimeng; Kozai, Mina; Mita, Hironobu; Takeuchi, Hiroto; Mizuno, Satoru; Matsuo, Kazuhiro; Takada, Kensuke (Frontiers in Immunology, 2025)
BackgroundMemory CD8+ T cells sense inflammation and rapidly produce interferon-γ (IFN-γ) independent of cognate antigens. This innate-like property, called bystander activation, is involved in early host defense before the antigen-specific memory response. However, the molecular mechanisms underlying this activation remain unknown. Retinoic acid receptor-related orphan receptor α (RORα) belongs to the nuclear receptor family and regulates gene transcription in ligand-dependent manner. Although RORα is highly expressed in memory CD8+ T cells, its functional relevance has not been investigated.MethodsPrimary and secondary memory T cells that are sufficient or deficient of RORα were induced by adoptive transfer of naïve OT-I T cells to recipient mice and subsequent infection with Listeria monocytogenes expressing ovalbumin (LM-OVA). RORα expression in memory T cells was examined by quantitative PCR. The target genes of RORα in memory T cells were explored by RNA-sequencing and verified by RORα overexpression in postactivated T cells. The impact of RORα-deficiency on bystander activation was assessed by stimulating memory T cells with inflammatory cytokines in vitro or injecting lipopolysaccharide (LPS) into mice bearing memory T cells.ResultsRORα expression was remarkably elevated in secondary memory CD8+ T cells along with the enrichment of effector-like memory T cells. RORα primarily acted as a transcription factor in regulating the gene expression of the TL1A receptor. RORα deficiency abrogated the IFN-γ production by memory CD8+ T cells in response to IL-12 + TL1A in vitro and diminished the bystander response to LPS-induced inflammation in vivo.ConclusionThis study revealed a regulatory mechanism of bystander activation. The findings also improve our understanding of how memory T cells increase their immediate protective capacity through repeated infections and vaccinations.